The outcome of coaching and training for self-employment. A statistical evaluation of outside assistance support programs for unemployed business founders in Germany - Dirk Oberschachtsiek; Patrycja Scioch (Journal for Labour Market Research, 2015)
This paper focuses on the question of whether improving the competence of new business founders through programs that offer external expertise enhances the duration of self-employment. In our analysis, we focus on three different programs that are provided along with a financial subsidy and that focus on founders who started a business while they were unemployed. We found that participation was strongly determined by regional patterns and time, and that individual characteristics were less important. These results reflect a particular regional specialization in promoting self-employment. A statistical matching approach was used to control for selectivity and was performed in a way that explicitly considered differences across regions and over time. The results show that the treatment effects tended to be low. However, we found evidence that external expertise increased passive learning.
Keywords: J68; J23; 330; Arbeitslose; Unternehmensgründung; Unternehmer; Coaching; arbeitsmarktpolitische Maßnahme - Erfolgskontrolle; Qualifizierungsmaßnahme; Unternehmenserfolg; Förderungsmaßnahme - Inanspruchnahme; regionale Faktoren; berufliche Selbständigkeit; Überbrückungsgeld; Integrierte Erwerbsbiografien; IAB-Betriebs-Historik-Panel; freie Förderung